2018
DOI: 10.1142/s2047684118500197
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetic ordering in gadolinium-doped AlGaN from LSDA + U calculations

Abstract: We present first-principles calculations of the structural, electronic and magnetic properties of Gd-doped [Formula: see text] based on the density functional theory within [Formula: see text] schemes. It is found that Gd atom favors substituting for Al site. Compared with undoped [Formula: see text], the Gd-doped [Formula: see text] has become an indirect band gap semiconductor of reduced band gap. The magnetic moment [Formula: see text] per molecule mainly comes from Gd ion with little contribution from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…It has been observed that these temperature values are acceptable. For the Fe atom, the obtained Curie temperature value is in a good agreement with the results reported in [52]. This could be exploited in high temperature nano-devices activities.…”
Section: Magnetic Propertiessupporting
confidence: 88%
“…It has been observed that these temperature values are acceptable. For the Fe atom, the obtained Curie temperature value is in a good agreement with the results reported in [52]. This could be exploited in high temperature nano-devices activities.…”
Section: Magnetic Propertiessupporting
confidence: 88%
“…The full potential linear augmented plane wave plus local orbital (FP-LAPW+lo) approach, as used in the Wien2K code [16], has been used to do the calculations pertaining to CuAl 0.25 Ga 0.75 Se 2 . This methodology has already been employed in our prior work and other works [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. It is based on density functional theory (DFT) [35,36].…”
Section: Methodology and Details Of Calculationsmentioning
confidence: 99%
“…Using OMVPE-grown GaN: Eu as an active layer, electroluminescence from a GaN-based LED has been successfully shown [27]. In our previous study, we demonstrated that AlGaN: RE (RE = Tm, Gd, Eu, Er) [28][29][30] and InGaN: RE (RE = Er, Eu, Tm) [31,32] exhibit a semiconductor character with a magnetic moment of 6.00, 3.00, 1.98, 7.15, and 3.02 for AlGaN: Eu, AlGaN: Er, AlGaN: Tm, AlGaN: Gd, and InGaN: Er, respectively. Akazawa et al [33] investigate the behaviour of Eu 3+ and Er 3+ ions when they are simultaneously introduced into ZnO thin lms.…”
Section: Introductionmentioning
confidence: 99%